1999
DOI: 10.1038/sj.gene.6363642
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variants in the interleukin-6 gene and essential hypertension in Japanese women

Abstract: Genes that can be implicated in hypertension in experimental animals are plausible candidates in the pathogenesis of human hypertension. A recent genome-wide search for quantitative-trait loci (QTL) in hypertensive rats revealed a strong correlation between the interleukin-6 (IL-6) locus on rat chromosome 4 and systolic, diastolic, and mean arterial pressure in this mammalian species. To investigate a possible association between genetic variations of the IL-6 gene and hypertension in humans, we identified two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
32
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 19 publications
7
32
0
Order By: Relevance
“…A recent study, performed in Japanese women, has found a weak association between some polymorphisms of the IL-6 gene promoter and hypertension. 29 This study analysed the C/G substitution at −634, the G/A substitution at 4391 in a 3Ј non-coding portion of exon 5, and the A/T variation in the −447 position. However, all these gene variants are different from that investigated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study, performed in Japanese women, has found a weak association between some polymorphisms of the IL-6 gene promoter and hypertension. 29 This study analysed the C/G substitution at −634, the G/A substitution at 4391 in a 3Ј non-coding portion of exon 5, and the A/T variation in the −447 position. However, all these gene variants are different from that investigated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It is known as an important risk factor for cardiovascular, renal disease and stroke but the underlying mechanisms of how high blood pressure cause to cardiovascular disease (CVD) are still uncertain. It leads to poor life quality and increases morbidity and mortality (Li et al 2005, Chae et al 2001Nakajima et al 1999;Johansson 1999). However molecular mechanisms of hypertension are not fully understood, the inflammation is known to be playing an essential role in pathogenesis of hypertension and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The IL-6 gene is located at p21 of chromosome 7, contains a 1.3 kb coding sequence with five exons and encodes a 23.7 kd protein. It is a polymorphic gene which -634 C/G, -598 A/G, -597 G/A, -572 G/C, -174 G/C polymorphisms were identified in its promoter region (Wang et al 2011;Nakajima et al 1999;Sesso et al 2006;Gao et al 2011;Jenny et al 2002;Baumann and Gauldie 1994;Wypasek et al 2010;Tanaka et al 2005;Sanders et al 2009;Timasheva et al 2008;Kitamura et al 2002;Illig et al 2004). Therefore most of the studies on IL-6 gene focus on promoter region polymorphism analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The G allele is associated with an increased inflammatory response in vivo and the occurrence/prognosis of various diseases, including cancer, Alzheimer's disease, atherosclerosis, cardiovascular disease, non -insulin-dependent diabetes mellitus, osteoporosis, and systemic onset juvenile chronic arthritis (10, 11, 14 -20). In Asian populations, however, this SNP is very rare (21 -23) and a more common and important SNP at position -634 (C>G) in the promoter region has been reported (22). The -634G allele has been associated with increased production and secretion of IL-6 by peripheral blood mononuclear cells in vitro (12).…”
mentioning
confidence: 99%